Reestructuración técnico administrativa de la empresa Misterio Beer S.A.S., ubicada en el municipio de Cajicá (2019)
The technical-administrative restructuring of the present degree project was developed in the municipality of Cajicá, its realization was subject to the recommendations and decisions made by the manager, the scope of this project ranges from the lifting of the administrative technical restructuring to the support and approval of the degree work. A financial study was carried out in order to determine the viability, feasibility and profitability of the project. The main objective of this restructuring is to improve the production process of artisanal beer in the Misterio Beer SA..S. plant. In order to carry out this objective, an external and internal diagnosis of the subsector was made to know the current situation, through a market study determine the target customer to search for new market niches, prepare a technical and environmental study to determine the improvement options in each area, carry out the administrative study with the purpose of a strategic plan in the company and to finalize a financial study to determine the feasibility of the project and profitability of purchasing a bottling plant.